Grain growth modeling for gas pressure sintering of silicon nitride based ceramics. (March 2023) - Grippi, Thomas; Béhar-Lafenetre, Stéphanie; Friedrich, Holger; Haas, Daniel; Schenderlein, Uwe; Marinel, Sylvain; Manière, Charles
Abstract: The complexity of liquid phase sintering of silicon nitride implies the use of advanced gas pressure sintering (GPS) industrial process. Sintering additives have been jointly developed to allow the sintering of this challenging material to reach high mechanical properties. The latter properties and GPS process of silicon nitride are strongly influenced by the microstructure development during the thermal treatment under temperature close to 1800 °C. In particular, grain growth is a key parameter that needs to be identified. In this work, an experimental design is used to explore microstructural development during the final stage of sintering. The grain size, and porosity data are extracted for different holding times and temperatures to allow the identification of the experimental grain growth. The study is extended to the impact of the heating kinetics regime and the influence of the gas pressure furnace environment. Graphical Abstract: Si3N4 gas pressure liquid phase sintering grain growth modeling. ga1